An electronic alert to decrease Kayexalate ordering. (25th November 2016) - Leaf, David E.; Cheng, Xingxing S.; Sanders, Jason L.; Mendu, Mallika; Schiff, Gordon D.; Mount, David B.; Bazari, Hasan
Abstract: Important safety concerns have recently emerged regarding the use of sodium polystyrene sulfonate (Kayexalate), a cation-exchange resin commonly used for the treatment of hyperkalemia. We implemented an electronic alert system at a tertiary care academic medical center to warn providers of the safety concerns of Kayexalate. We assessed the number of Kayexalate prescriptions per month, as well as the number of grams of Kayexalate ordered per month, one year before versus one year after implementing the alert. The mean (±SD) number of Kayexalate orders decreased from 123 (±12) to 76 (±14) orders/month (38% absolute reduction, p <  0.001) after implementing the alert. Additionally, the mean (±SD) amount of Kayexalate prescribed decreased from 3332 (±329) to 1885 (±358) g/month (43% absolute reduction, p <  0.001). We conclude that an electronic alert is an effective tool to decrease Kayexalate ordering.